Survey of Snail And Slug Pests On Agricultural Land In Java (Gastropoda : Pulmonata) - Mujiono Nova (Masyarakat Moluska Indonesia, 2019)
The diversity of terrestrial gastropods as horticultural pests in Java has been examined. Six species of gastropoda, of which three species are snail and three others are slug, were collected and identified from 18 host-plant species from 20 observed locations. Some of them are economically destructive. Bradybaena similaris is capable of attacking 18 plant species, while Parmarion martensi also capable of attacking 10 plant species. Both species are potentially detrimental for local farmers. This paper will deal with the morphological identification and distribution of each species, as well as their attack and impact to their host-plant species.